Analisis Pendapatan Peternak Ayam Broiler di Kecamatan Ringinrejo Kabupaten Kediri - MUFIDA, ILMI; SUDARMA, I MADE; DEWI, RATNA KOMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023DO - 10.24843/JAA.2023.v12.i01.p19, 2023)
Income Analysis of Broiler Breeders in Ringinrejo District, Kediri Regency A lot of broiler chicken farming businesses experience up and down. Breeders don't always get high profits. The purpose of this study is to analyze the quantity of income and to analyze the product factors that influence the quantity of product of broiler farms for partnership and independent patterns in Ringinrejo District, Kediri Regency. The research is conducted in Selodono and Sambi Village, Ringinrejo District, Kediri Regency, East Java Province. The types of data used are qualitative and quantitative data sourced from primary data and secondary data. The method of data collection is carried out by observation and interview. The results show that the partnership pattern receives lower income for each kg chicken than the independent pattern, which is Rp 1.068,00 while the independent pattern is Rp 3.099,00. Furthermore, the result of the analysis shows that the quantity of DOC and the quantity of feed partially have a positive and significant effect on the quantity of product, while the area of the cage has a negative and significant effect. The other variables partially have no significant effect on the quantity of product. The independent pattern of broiler farming is more profitable because income of the independent pattern is higher than the partnership pattern. Before starting production, breeders have to look at the market conditions to find out the purchase price and the selling price of livestock.